Employee training and wage dispersion: white and blue collar workers in Britain - Filipe Almeida-Santos; Yekaterina Chzhen; Karen Mumford (Institute for the Study of Labor (IZA), 2010)
We use household panel data to explore the wage returns associated with training incidence and intensity (duration) for British employees. We find these returns differ depending on the nature of the training; who funds the training; the skill levels of the recipient (white or blue collar); the age of the employee; and if the training is with the current employer or not. Using decomposition analysis, training is found to be positively associated with wage dispersion: a virtuous circle of wage gains and training exists in Britain but only for white-collar employees.
Keywords: J24; J31; J41; 330; Training; wage compression; performance; Personalentwicklung; Betriebliche Bildungsarbeit; Lohnstruktur; Angestellte; Arbeitskräfte; Bildungsertrag; Großbritannien